Transmission and re-infection of Omicron variant XBB.1.5 in hamstersResearch in context - Peter J. Halfmann; Ryuta Uraki; Makoto Kuroda; Kiyoko Iwatsuki-Horimoto; Seiya Yamayoshi; Mutsumi Ito; Yoshihiro Kawaoka (EBioMedicine, 2023)
Summary: Background: Like its predecessors in the XBB family, XBB.1.5 is highly immune evasive from therapeutic monoclonal antibodies and neutralizing antibodies generated by vaccination and/or infection. However, there is a lack of in vivo data on XBB.1.5 in animal models such as Syrian hamsters. Methods: Syrian hamsters (females) were used to examine airborne transmission along with virus replication of XBB.1.5 in naïve animals and human ACE2 hamsters with pre-existing immunity from a previous infection with Omicron BA.1. Assays were performed to determine neutralizing antibody responses, and virus titers were determined by standard plaque assays. Findings: Unlike earlier Omicron subvariants, such as BA.1 and BA.2, XBB.1.5 transmitted more efficiently in the hamster model. In addition, XBB.1.5 partially escaped BA.1-immunity from a previous infection with XBB.1.5 replicating in the nasal turbinate tissues and to a lesser extend in the lung tissues of previously infected hamsters. Interpretation: Our in vivo data showing better airborne transmissibility of the Omicron subvariant XBB.1.5 than its predecessor, BA.2, in Syrian hamsters will allow researchers to further investigate amino acid substitutions that give XBB.1.5 a fitness advantage over BA.2 in transmission, data that may be important in studies of SARS-CoV-2 transmission in humans. Funding: This research is supported by grants from the Center for Research on Influenza Pathogenesis and Transmission (CRIPT; 75N93021C00014), funded by the National Institute of Allergy and Infectious Diseases and by a Research Program on Emerging and Reemerging Infectious Diseases (JP21fk0108552 and JP21fk0108615), a Project Promoting Support for Drug Discovery (JP21nf0101632), the Japan Program for Infectious Diseases Research and Infrastructure (JP22wm0125002), and The University of Tokyo Pandemic Preparedness, Infection and Advanced Research Center (UTOPIA) grant (JP223fa627001) from the Japan Agency for Medical Research and Development.